Remote monitoring of implantable cardioverter defibrillators: Patient experiences and preferences for follow‐up. Issue 2 (2nd January 2019) - Timmermans, Ivy; Meine, Mathias; Szendey, Istvan; Aring, Johannes; Romero Roldán, Javier; van Erven, Lieselotte; Kahlert, Philipp; Zitron, Edgar; Mabo, Philippe; Denollet, Johan; Versteeg, Henneke
Abstract: Background: Patient satisfaction with remote patient monitoring (RPM) of implantable cardioverter defibrillators (ICDs) seems to be high, yet knowledge on long‐term patient experiences is limited. The European REMOTE‐CIED study explored patients' experiences with RPM, examined patient's preferences for ICD follow‐up, and identified determinants of patient's preferences in the first 2 years postimplantation. Methods: European heart failure patients ( N = 300; median age = 66 years [interquartile range (IQR) = 59‐73], and 22% female) with a first‐time ICD received a Boston Scientific LATITUDE RPM system (Marlborough, MA, USA) and had scheduled in‐clinic follow‐ups once a year. Patients completed questionnaires at 1‐2 weeks and also at 3, 6, 12, and 24 months postimplantation and clinical data were obtained from their medical records. Patient evaluation data were analyzed descriptively, and Student's t ‐tests/Man‐Whitney U tests or Chi‐square tests/Fisher's exact tests were performed to examine determinants of patient preferences. Results: At 2 years postimplantation, the median patient satisfaction score with the RPM system was 9 out of 10 (IQR = 8‐10), despite 53% of the patients experiencing issues (eg, failure to transmit data). Of the 221 patients who reported their follow‐up preferences, 43% preferred RPM and 19% preferred in‐clinic follow‐up. Patients with a preference for RPM were more likely to be higher educated ( P = 0.04), employed ( P = 0.04), and equipped with a new LATITUDE model ( P = 0.04), but less likely to suffer from chronic obstructive pulmonary disease ( P = 0.009). Conclusion: In general, patients were highly satisfied with RPM, but a subgroup preferred in‐clinic follow‐up. Therefore, physicians should include patients' concerns and preferences in the decision‐making process, to tailor device follow‐up to individual patients' needs and preferences.